The Role of Modern Management in the Field of Entrepreneurship in Uzbekistan and the Problem of its Implementation (Texas Journal of Multidisciplinary Studies, 2022)
This article describes the current state of management in Uzbekistan the problem and prospect for the introduction of modern management in business